Penerapan Kegiatan Senam Ceria Untuk Meningkatkan Motorik Anak Usia Dini di TK ABA Kartini Cabang Kota Binjai - Halimah Fitri; Rita Nofianti; Rahayu Dwi Utami (Early Childhood Research and Practice, 2026)
This study aims to describe how cheerful gymnastics activities can help improve the gross motor skills of early childhood students at TK ABA Kartini. The background of the research is based on the importance of physical stimulation during the golden age and the requirements of the early childhood education curriculum, which encourages the use of rhythmic movement activities. The study employed a descriptive qualitative method with 20 children as subjects. Data were collected through observation, interviews, and documentation. The findings indicate that cheerful gymnastics, when carried out routinely through stages of warm-up, core movements, and cool-down, can enhance children’s balance, coordination, agility, strength, and flexibility. The children appeared more active, enthusiastic, and able to follow movement patterns well. Teachers played an essential role in demonstrating movements, organizing activities, and creating an enjoyable learning atmosphere through cheerful music. Challenges such as differences in children's motor abilities could be addressed through movement adjustments and additional guidance. Overall, cheerful gymnastics proved effective as a form of gross motor stimulation and can be integrated as a regular component of the learning program at TK ABA Kartini.